Stochastic Modelling and Analysis of Driver Behaviour - Cerone, Antonio; Zhao, Yishi (Electronic Communications of the EASST, 2014)
Driver behaviour is considered a key factor in the majority of car accidents. As a consequence driver behaviour has been receiving vast attention in different domain areas, such as psychology, transport engineering and computer science. Computer scientists are primarily interested in what and how computing means can be applied to understand the relation between driver behaviour and transport systems. In this paper, we adopt a stochastic approach to conduct a quantitative investigation of driver behaviour. We use the Markovian process algebra PEPA (Performance Evaluation Process Algebra) to describe the overall system model. The system component describing the topology and dynamic of the traffic is composed in parallel with the system component describing the driver state and its evolution due to experience. We illustrate our approach using a three-way junction as an example and present the numerical results of the system analysis.